Conserved community structure and simultaneous divergence events in the fig wasps associated with Ficus benjamina in Australia and China - Darwell, Clive T; Segar, Simon T; Cook, James M (BMC ecology, 2018)
BACKGROUND: Localised patterns of species diversity can be influenced by many factors, including regional species pools, biogeographic features and interspecific interactions. Despite recognition of these issues, we still know surprisingly little about how invertebrate biodiversity is structured across geographic scales. In particular, there have been few studies of how insect communities vary geographically while using the same plant host. We compared the composition (species, genera) and functional structure (guilds) of the chalcid wasp communities associated with the widespread fig tree, Ficus benjamina, towards the northern (Hainan province, China) and southern (Queensland, Australia) edges of its natural range. Sequence data were generated for nuclear and mtDNA markers and used to delimit species, and Bayesian divergence analyses were used to test patterns of community cohesion through evolutionary time. RESULTS: Both communities host at least 14 fig wasp species, but no species are shared across continents. Community composition is similar at the genus level, with six genera shared although some differ in species diversity between China and Australia; a further three genera occur in only China or Australia. Community functional structure remains very similar in terms of numbers of species in each ecological guild despite community composition differing a little (genera) or a lot (species), depending on taxonomic level. Bayesian clustering analyses favour a single community divergence event across continents over multiple events for different ecological guilds. Molecular dating estimates of lineage splits between nearest inter-continental species pairs are broadly consistent with a scenario of synchronous community divergence from a shared "ancestral community". CONCLUSIONS: Fig wasp community structure and genus-level composition are largely conserved in a wide geographic comparison between China and Australia. Moreover, dating analyses suggest that the functional community structure has remained stable for long periods during historic range expansions. This suggests that ecological interactions between species may play a persistent role in shaping these communities, in contrast to findings in some comparable temperate systems.
Keywords: Biodiversity; China; Austrálie; Barcoding; fylogeneze; Sequence Analysis, DNA; Phylogeny; potravní řetězec; sekvenční analýza DNA; hmyzí proteiny; Community composition; biologická evoluce; respirační komplex IV; společenstvo; Parasitoid; mezerníky ribozomální DNA; Food Chain; Electron Transport Complex IV; Animals; Ficus; Galler; Biological Evolution; Chalcidoidea; Wasp; zvířata; Biota; Insect Proteins; DNA, Ribosomal Spacer; Čína; sršňovití; Wasps; Australia